The development model of synchronization of teaching-learning Indonesian language and literature using quantum learning approach - Budhi Setiawan,; Herman J.Waluyo,; Nugraheni Eko Wardani, (Fakulti Sains Sosial dan Kemanusiaan, 2010)
This paper elaborates the principle of quantum learning in the teaching-learning of language and literature, a method that has been developed by synchronizing the process with the orchestral atmosphere (with musical accompaniment). Data for configuring the principle were collected from the continuous, intensive research undertaken in seven SMP’s (Junior High School) in Surakarta Province, Indonesia, since the 1990s. It is found that the boredom among the students in the class room, especially during the teaching-learning of language and literature sessions, could be lessened by creating orchestral atmosphere as it could arouse the students’ attention, interest, and motivation in learning. The practicality and usefulness of this method in the teaching-learning process, especially of ‘dry,’ boredom subjects such as language and literature, is proven by the result of this research which had been published by the supporship of stakeholders (especially the authority) in Surakarta Province and being accepted by the authority to be used in the SMP’s in the province.